Social Transfer Multipliers in Developed and Emerging Countries : The Role of Hand-to-Mouth Consumers - Bracco, Jessica; Galeano, Luciana; Juarros, Pedro; Riera-Crichton, Daniel; Vuletin, Guillermo (World Bank, Washington, DC, 2021)
This paper estimates the macroeconomic effects of social transfer payments to individuals for a sample of 23 developed and Latin American countries. The findings show that the social transfer multiplier is 0.3 in developed countries, but 0.9 in Latin American economies. The paper studies the role of hand-to-mouth consumers, who have no access to financial markets and a high marginal propensity to consume, as a first order factor to explain the heterogeneity in the size of social transfer multipliers. Using survey-based data from the Global Findex dataset, the paper finds that the average share of the population living hand-to-mouth is 23 percent in developed economies versus 60 percent in Latin American countries. This evidence is interpreted with a two-agent New Keynesian model. The findings show that the difference in the share of hand-to-mouth consumers explains 80 to 90 percent of the difference in the estimated social transfer multipliers. The paper also documents that the share of hand-to-mouth individuals in emerging countries is in general 47 percent which suggests that a larger social transfer multiplier may be expected for this type of economy.